Outcome of patients with early ovarian cancer undergoing three courses of adjuvant chemotherapy following complete surgical staging. Issue 4 (1st June 2005) - Shimada, M.; Kigawa, J.; Kanamori, Y.; Itamochi, H.; Oishi, T.; Minagawa, Y.; Ishihara, K.; Takeuchi, Y.; Okada, M.; Terakawa, N.
Abstract : We conducted the present study to determine the outcome of patients with early ovarian cancer who underwent three courses of adjuvant chemotherapy after complete surgical staging. One hundred consecutive patients with stage I–II epithelial ovarian cancer who had undergone complete surgical staging and received three courses of platinum-based chemotherapy were entered in this study. Twenty-one patients were low risk, defined as stage IA–B, grade 1 and histologic types except for clear cell adenocarcinoma, and remaining 79 were high risk. All patients with stage IA or IB, whatever histologic type and histopathologic grade, were alive without disease. The 5-year survival rate was 89.4% for patients with stage IC and 76.2% for those with stage II. The 5-year survival rate for low- and high-risk patients was 100% and 89.4%, respectively. The survival rate for grade 1 was significantly better than that for grade 2 or 3. Multivariate analysis revealed that histologic grade was an independent prognostic factor in stage IC–II ovarian cancer. The outcome of patients with early ovarian cancer undergoing three courses of chemotherapy after complete surgical staging was favorable even in high-risk patients